2014
DOI: 10.1177/1461445613519018
|View full text |Cite
|
Sign up to set email alerts
|

Managing employees’ talk about problems in work in performance appraisal interviews

Abstract: Performance appraisal interviews are carried out on the basis of known-in-advance written materials such as preparation forms and interview guides. This article demonstrates how participants manage interviews by following a question–answer–response format fit to address interview guide entries one at a time. Two recurring supervisor responses to employees’ talk about problems in work are investigated: positive prediction and advice. It is suggested that these responses serve to establish supervisor authority a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(59 reference statements)
0
4
0
1
Order By: Relevance
“…Ongelmien käsittely on kuitenkin todettu hankalaksi. Yhtäältä on ajateltu, että syynä tähän on kehityskeskustelujen tavoitteellisuus ja johtopäätöksiin pääseminen, jolloin keskustelun muodollinen rakenne ja keskustelussa käytettävät, muodollista rakennetta tukevat tekstidokumentit (Lehtinen & Pälli, 2021) tukevat ainoastaan päätöksentekopyrkimyksiä, ei ongelmien käsittelyä (Scheuer, 2014). Toisaalta esihenkilöillä on mahdollisuus ohjata keskusteluja haluamaansa suuntaan (Asmuß, 2008;Mikkola, 2014).…”
Section: Tendenssikertomukset Kehityskeskusteluissaunclassified
“…Ongelmien käsittely on kuitenkin todettu hankalaksi. Yhtäältä on ajateltu, että syynä tähän on kehityskeskustelujen tavoitteellisuus ja johtopäätöksiin pääseminen, jolloin keskustelun muodollinen rakenne ja keskustelussa käytettävät, muodollista rakennetta tukevat tekstidokumentit (Lehtinen & Pälli, 2021) tukevat ainoastaan päätöksentekopyrkimyksiä, ei ongelmien käsittelyä (Scheuer, 2014). Toisaalta esihenkilöillä on mahdollisuus ohjata keskusteluja haluamaansa suuntaan (Asmuß, 2008;Mikkola, 2014).…”
Section: Tendenssikertomukset Kehityskeskusteluissaunclassified
“…In appraisal interviews, for example, lack of active listening is not necessarily simply a skills-related problem, but rather an enactment of supervisory authority. Scheuer (2014) found that lack of active listening cues (such as backchannel signals, repetition of what has been said, probing questions and non-verbal cues such as nodding) might come across as a professional effort to give employees the space to talk. However, such behavior takes from employees the chance to actually engage in a discussion about the problems they experience.…”
Section: Language and Discourse Awareness In Management Education 16mentioning
confidence: 99%
“…The importance of this agenda cannot be overstated. It is hard to find an area of organizational life where such a critical lens would not be warranted: from exposing the cultural and linguistic disadvantage of candidates in promotion and job interviews (and challenging managers’ own cultural predispositions) (Roberts, 2011; Roberts & Campbell, 2005; Scheuer, 2014) to critically examining the function and appropriateness of linguistic practices such as teasing, jocular abuse, swearing, and rudeness in management discourse (Ladegaard, 2012; Mak & Darics, 2017; Schnurr, 2009), and from understanding how cultural, linguistic, and gender differences manifest in communication and influence participation in and management of workplace activities (Alvesson & Billig, 1997; Angouri, 2010, 2018; Baxter, 2011) to exposing the role of language in justifying questionable business decisions (Amernic & Craig, 2006; Spicer, 2018) or shifting blame and avoiding responsibility (Darics & Koller, 2019; Hargie et al, 2010). The final step is therefore to embrace the critical stance: Management education needs to encourage students to use their knowledge to challenge the taken-for-granted, as a way to not only nurture higher order cognitive skills but also develop self-reflexive, responsible management practice in the hope of challenging unfair work practices (see Roberts, 2011).…”
Section: Understanding Communication As a Process Of Social Constructionmentioning
confidence: 99%
“…While there have been a number of studies of criticisms that are designed to suggest or even require that the fault in question be redressed, we still know very little about criticisms where the aim is to insult or wound the target (Tayebi 2018). Empirical studies have focused for the most part on examining criticisms in institutional contexts, including in appraisal meetings in which supervisors are evaluating work performance (Asmuß 2008;Copland 2011;Schuer 2014;Tracy & Eisenberg 1990/91), in feedback sessions where academic work is being evaluated (Li & Seale 2007;Nguyen 2008), or in parent-teacher interviews in which students' work is being reported upon (Pillet-Shore 2015, 2016. In such contexts, criticisms are licensed by the roles of participants in those settings.…”
Section: Prior Research On Criticismsmentioning
confidence: 99%